Faktor-Faktor Penentu Keputusan Mahasiswa dalam Memilih Perguruan Tinggi: Studi Empiris pada Kampus X di Makassar - Wijaya, Hans Christian; Tungadi, Derryl; Wanggarry, Veron; Christoffel, Robin Christoffel; Sanapang, Gracela Marisa (Jurnal Online Manajemen ELPEI, 2025)
This study aims to analyze the factors that influence students' decisions in choosing a campus, focusing on academic variables, facilities & resources, finance, social and cultural, location, marketing strategy, and student experience. Using the Theory of Planning Behavior (TPB) approach, this study explores how attitudes, subjective norms, and behavioral control of prospective students influence their decision making. Data were collected through a survey of 385 students at one of Campus X in Makassar City using the stratified random sampling method. The data analysis technique used PLS-SEM. The results showed that location and student experience had a significant influence on students' intention to choose a campus, while academic variables, facilities & resources, finance, social and cultural, and marketing strategy did not have a significant influence. Location factors, including ease of access, security, and a supportive environment, proved to be one of the main drivers. In addition, student experience in the form of testimonials and levels of satisfaction contributed strongly to campus selection decisions. The implications of this study highlight the importance of higher education institutions to focus on improving location strategies and strengthening positive student experiences as the main attraction. Marketing strategies also need to be adjusted to be more relevant to the needs of prospective students and can increase the credibility of the institution amidst competition in the education market.